Cavernous hemangioma in the floor of oral cavity masquerading as a ranula - Puneeta Vohra; Vinod Vijay Chandar; Ranjit Patil; Saumya Verma (Wolters Kluwer Medknow Publications, 2015)
A painless, bluish, submucosal swelling on one side of the floor of the mouth usually indicates the presence of a ranula. Rarely, such a swelling may be caused by an inflammatory disease process in a salivary gland, a neoplasm in the sublingual salivary gland, hemangiomas, a lymphatic nodular swelling, amyloidosis, or embryologic cysts/dermoid cyst. We report a 35-year-old female patient with swelling in the floor of her mouth that was clinically diagnosed as a ranula due to negative diascopy, the site of swelling, and the age of patient. Because of a strong clinical suspicion of a ranula, diagnostic methods such as angiography and magnetic resonance imaging (MRI) were not used in our case. A preoperative diagnosis was not truly established. We report a case of hemangioma in the floor of the mouth masquerading as a ranula. Although a rarity, vascular malformations should always be ruled out by using digital subtraction angiography and MRI studies before going for surgical intervention.